The Spell of the Yukon and Other Verses - Service, Robert W. (Robert William), 1874-1958 (Salt Lake City, UT : Project Gutenberg, 1995)
"The Spell of the Yukon and Other Verses" by Robert W. Service is a poetry collection published in 1907. Written by a bank employee in Whitehorse who had never seen the Klondike Gold Rush firsthand, these verses capture the spirit of Yukon frontier life through vivid storytelling. The collection features famous humorous ballads like "The Shooting of Dan McGrew" and "The Cremation of Sam McGee," poems born from overheard saloon revelry and campfire tales. This wildly successful book sold over three million copies and made Service a celebrated poet before he ever set foot in Dawson City. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Songs_of_a_Sourdough
Release date is 1995-01-01
Produced by A. Light, G.L. Warner, and David Widger
Keywords: Yukon River Valley (Yukon and Alaska) -- Poetry